005 Infusion associated reactions in ocrelizumab-treated multiple sclerosis patients. Issue 6 (27th May 2022) - Das, Esther; Bewick, Claire; Collins, Justine; Nash, Cynthia; Fisniku, Leonora
Abstract : Background and aims: Infusion-associated-reactions (IARs) are a common side effect (SE) of Ocrelizumab, a disease modifying therapy (DMT) licensed for treatment of Multiple Sclerosis (MS). Tolerability is an important factor patients take into account when selecting a DMT. We sought to assess the frequency of IARs in the Ocrelizumab-treated MS-patients at Brighton & Sussex University Hospitals MS-Centre. Methods: All Ocrelizumab-treated MS-patients data from February 2019 to January 2020 was reviewed. IARs classified as mild, moderate, severe and life-threatening as per Ocrelizumab proforma, during and 1-hour post infusion were recorded. Patients were advised to contact the infusion nurses if they experi- enced further symptoms in the next 24-hours post infusion. Results: 28-patients received Ocrelizumab: 20(71%) females; mean age 41.7 years old (range 25–58); median EDSS 2 (range 0–6). 12(42.8%) patients had received no prior DMTs. 23(82.1) patients reported either nil or mild IARs; 7(25%) patients had mild IAR. 2(7.1%) patients had moderate IAR; 2(7.1%) patients had severe IAR, 1(3.6%) patient experiencing throat pain, swelling, rhinorrhoea and dyspnoea. 1(3.6%) patient experienced significant raised liver enzymes; 1(3.6%) patient had acute respiratory distress syndrome requiring treatment discontinuation. Conclusion: Our data suggest that Ocrelizumab is generally well tolerated, however caution should be exercised and patient should be monitored closely especially in the initial infusion. Real world data provides useful information to share with patients when they are consented. leonora.fisniku@nhs.net